Cancer stem cell populations in lymphoma in dogs and impact of cytotoxic chemotherapy. (21st October 2018) - Hartley, Genevieve; Elmslie, Robyn; Murphy, Brent; Hopkins, Leone; Guth, Amanda; Dow, Steven
Abstract : Cancer relapse following chemotherapy has been attributed in part to the presence of cancer stem cells (CSC), which drive tumour growth and metastasis and are highly resistant to the effects of cytotoxic chemotherapy. As a result, treatment with cytotoxic chemotherapy selects for drug‐resistant CSC populations that eventually drive tumour recurrence. Little is known currently regarding the role of CSC in dogs with lymphoma, nor the impact of chemotherapy on CSC populations. Therefore, we prospectively quantitated CSC populations in dogs with B‐cell (BCL) and T‐cell lymphoma (TCL), using tumour aspirates and flow cytometric analysis with a panel of CSC markers. In addition, in vitro studies were carried out to determine the impact of chemotherapy resistance on the stem cell phenotype and stem cell properties of lymphoma cells. We found that the percentages of tumour cells expressing CSC markers were significantly increased in dogs with BCL, compared with B cells from normal lymph nodes. Similar findings were observed in dogs with TCL. In vitro studies revealed that lymphoma cells selected for resistance to CHOP chemotherapy had significantly upregulated expression of CSC markers, formed spheroids in culture more readily, and expressed significantly greater aldehyde dehydrogenase activity compared with chemotherapy‐sensitive tumour cells. Similar results were observed in tumour samples dogs with relapsed BCL. These findings suggest that cytotoxic chemotherapy can lead to a relative enrichment of tumour cells with CSC properties, which may be associated with lymphoma recurrence.